2009
DOI: 10.1001/archoto.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mometasone Furoate to Prevent Polyp Relapse After Endoscopic Sinus Surgery

Abstract: clinicaltrials.gov Identifier: NCT00731185.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 21 publications
2
96
0
1
Order By: Relevance
“…The study authors were contacted via e-mail for raw data in cases of missing data. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The analyses were based on intention to treat. For missing standard deviations, either 95% CIs, 23,31,32 standard error.…”
Section: Discussionmentioning
confidence: 99%
“…The study authors were contacted via e-mail for raw data in cases of missing data. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] The analyses were based on intention to treat. For missing standard deviations, either 95% CIs, 23,31,32 standard error.…”
Section: Discussionmentioning
confidence: 99%
“…Stjärne, et al 15 reported that subjects who underwent FESS and were treated with mometasone furoate nasal spray resulted in a significantly longer relapse-free period than placebo in both the intention to treat (ITT) and the per protocol data sets. 15 …”
Section: Endoscopic Scoresmentioning
confidence: 99%
“…24 One cohort study (n ϭ 32) 18 reported normal ACTH levels measured before and 1 hour after removal of corticosteroid-soaked packing gauze. 18 The reported adverse events from the included studies were blood-stained mucus, [22][23][24][25] mild epistaxis, 15,17,19 and nasal dryness. 22,23,26 …”
Section: Standard-dose Versus High-dose Incsmentioning
confidence: 99%
“…Since the approval of MFNS in the US, a large, randomized, placebo-controlled double-blind multicenter trial found that MFNS prevented or prolonged the time to nasal polyp recurrence [86]. In this study, subjects who had undergone FESS to treat endoscopically verified bilateral NP were treated with MFNS 200 µg once daily or placebo.…”
Section: Resultsmentioning
confidence: 99%